Improving argumentative writing performance among Chinese EFL postgraduates using WeCWI-enabled TenCent docs / Chen Chen, Boon Yih Mah and Norhaslinda Hassan - Chen, Chen; Boon, Yih Mah; Hassan, Norhaslinda (Universiti Teknologi Mara Cawangan Pulau Pinang, 2025)
Argumentative writing is a type of academic writing that involves defending a specific viewpoint on a debatable issue to persuade the reader of its validity. Web-based Cognitive Writing Instruction (WeCWI) emphasises technology-enhanced explicit writing instruction and promotes joint construction between peers and instructors, yielding positive outcomes through computer-mediated L2 writing. In addition, it increases the opportunity for English input and output. This study examines how the WeCWI-enabled tool, Tencent Docs, impacts argumentative writing performance among postgraduate English as a Foreign Language (EFL) students, addressing factors that lead to poor writing outcomes. A quasiexperimental design was employed, wherein two intact classes were randomly assigned to one of two conditions: (1) WeCWI-enabled writing instruction (n=56) and (2) conventional writing instruction (n=55). An independent-sample t-test was conducted, revealing that students in the experimental group significantly outperformed those in the control group regarding overall writing scores and in the sub-scores for argument effectiveness and organisation. The findings suggest that WeCWI-enabled writing instruction is more effective than conventional writing instruction for enhancing argumentative writing skills. This effectiveness is attributed to the greater emphasis placed on reading, online discussions, explicit instruction, joint construction and collaborative reviewing, facilitated by the affordances of Tencent Docs. This study’s implications are significant for enhancing argumentative writing skills among Chinese EFL learners. Consequently, it is recommended that WeCWI be expanded across a broader range of educational settings further to facilitate the development of students’ argumentative writing abilities.